The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adfm.202304286
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose and Chitin Twisted Structures: From Nature to Applications

Abstract: Twisted structures are ubiquitous in plants and animals. Cellulose and chitin are natural polymers that form the structural skeleton of various twisted systems observed across different length scales, ranging from the molecular to the nano, micro, and macro scale. In addition, cellulose and chitin helicoidal structures are found to be responsible for structural coloration, enhanced mechanical properties, and motion. This review first addresses cellulose and chitin‐based chiral molecular systems and nanoscale h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 234 publications
0
3
0
Order By: Relevance
“…Chiral nematic structures are known for their exceptional mechanical robustness, possessing multiple toughening mechanisms that enhance their mechanical properties. Chiral nematic structures are complex three-dimensional structures arranged in torsional layers . This structure is maintained by noncovalent bonding interactions, enabling the material to absorb external forces and dissipate energy efficiently through intermolecular motions and rearrangements .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral nematic structures are known for their exceptional mechanical robustness, possessing multiple toughening mechanisms that enhance their mechanical properties. Chiral nematic structures are complex three-dimensional structures arranged in torsional layers . This structure is maintained by noncovalent bonding interactions, enabling the material to absorb external forces and dissipate energy efficiently through intermolecular motions and rearrangements .…”
Section: Resultsmentioning
confidence: 99%
“…Chiral nematic structures are complex three- dimensional structures arranged in torsional layers. 64 This structure is maintained by noncovalent bonding interactions, enabling the material to absorb external forces and dissipate energy efficiently through intermolecular motions and rearrangements. 65 At the same time, the angular differences between the layers create barriers to crack extension and increase toughness by deflecting crack paths.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…This goes beyond the linear dependence of the modulus on the cross-link concentration, suggesting a more complex network configuration compared to that schematized in Figure B,C. Indeed, various authors report that cellulose chains in solution, in the presence of water, form heterogeneous bundles or ordered mesophases, depending on the grade of cellulose used. Also, Tharmann et al reported that the modulus of cross-linked actin gels varies with the power of 3.5 of the cross-linker concentration, and this was ascribed to the formation of actin chain bundles.…”
mentioning
confidence: 85%